Transcriptome, proteome and functional characterization reveals salt stress tolerance mechanisms in upland cotton (Gossypium hirsutum L.) - Sun, Kangtai; Mehari, Teame Gereziher; Fang, Hui; Han, Jinlei; Huo, Xuehan; Zhang, Jingxia; Chen, Yu; Wang, Dongmei; Zhuang, Zhimin; Ditta, Allah; Khan, Muhammad K.R.; Zhang, Jun; et al. (Frontiers in Plant Science, 2023)
Uncovering the underlying mechanism of salt tolerance is important to breed cotton varieties with improved salt tolerance. In this study, transcriptome and proteome sequencing were performed on upland cotton (Gossypium hirsutum L.) variety under salt stress, and integrated analysis was carried out to exploit salt-tolerance genes in cotton. Enrichment analysis using Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) was performed on differentially expressed genes (DEGs) obtained from transcriptome and proteome sequencing. GO enrichment was carried out mainly in the cell membrane, organelle, cellular process, metabolic process, and stress response. The expression of 23,981 genes was changed in physiological and biochemical processes such as cell metabolism. The metabolic pathways obtained by KEGG enrichment included glycerolipid metabolism, sesquiterpene and triterpenoid biosynthesis, flavonoid production, and plant hormone signal transduction. Combined transcriptome and proteome analysis to screen and annotate DEGs yielded 24 candidate genes with significant differential expression. The quantitative real-time polymerase chain reaction (qRT-PCR) validation of the candidate genes showed that two genes (Gh_D11G0978 and Gh_D10G0907) responded significantly to the induction of NaCl, and these two genes were further selected as target genes for gene cloning and functional validation through virus-induced gene silencing (VIGS). The silenced plants exhibited early wilting with a greater degree of salt damage under salt treatment. Moreover, they showed higher levels of reactive oxygen species (ROS) than the control. Therefore, we can infer that these two genes have a pivotal role in the response to salt stress in upland cotton. The findings in this research will facilitate the breeding of salt tolerance cotton varieties that can be grown on saline alkaline lands.